2019
DOI: 10.3892/or.2019.7183
|View full text |Cite
|
Sign up to set email alerts
|

miR‑29 promoter and enhancer methylation identified by pyrosequencing in Burkitt lymhoma cells: Interplay between MYC and miR‑29 regulation

Abstract: Deregulation of microRNA expression plays a significant role in several cancer types including Burkitt lymphoma (BL). MicroRNA genes may be regulated through epigenetic mechanisms, such as specific histone modifications and/or DNA methylation of CpG islands in promoter regions, or by regions that are located next to microRNA genes. Given the regulatory role of MYC in miR-29 expression, methylation as an additional mechanism for miR-29 silencing was investigated. Methylation of miR-29a/b/c in BL tumour samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
6
1
Order By: Relevance
“…Aberrant methylation of levels were observed in individuals diagnosed with specific subtypes of NHL when compared to controls, BL being the most prominent. An aggressive subtype of NHL, the BL cell line Raji was identified to exhibit increased methylation in these same regions in the cell line populations, and previous studies have reported a similar increase in methylation levels to those identified in this study in other miRNA promoter regions, in both BL cell lines and BL tumours (Mazzoccoli et al, 2018;Mazzoccoli et al, 2019). Increased methylation was also observed between CLL individuals and controls in region 1 of the MIR17HG, and a previous study identified that aberrant methylation of miRNA promoter regions in circulating B-cells of CLL patients was associated with abnormal miRNA expression when compared to healthy B-cells.…”
Section: Discussionsupporting
confidence: 85%
“…Aberrant methylation of levels were observed in individuals diagnosed with specific subtypes of NHL when compared to controls, BL being the most prominent. An aggressive subtype of NHL, the BL cell line Raji was identified to exhibit increased methylation in these same regions in the cell line populations, and previous studies have reported a similar increase in methylation levels to those identified in this study in other miRNA promoter regions, in both BL cell lines and BL tumours (Mazzoccoli et al, 2018;Mazzoccoli et al, 2019). Increased methylation was also observed between CLL individuals and controls in region 1 of the MIR17HG, and a previous study identified that aberrant methylation of miRNA promoter regions in circulating B-cells of CLL patients was associated with abnormal miRNA expression when compared to healthy B-cells.…”
Section: Discussionsupporting
confidence: 85%
“… 46 , 169 EBV miR-BART6-5p combined with dexitabine can enhance the expression of miR-29 in EBV-positive Burkitt lymphoma cell lines. 48 MiR-BART6-3p avoids RIG-I recognition by targeting RIG-I (a pattern recognition receptor), evades the host's innate immune response, and promotes EBV infection. 172 …”
Section: Mirnas Abnormally Expressed In Itpmentioning
confidence: 99%
“…46,169 EBV miR-BART6-5p combined with dexitabine can enhance the expression of miR-29 in EBV-positive Burkitt lymphoma cell lines. 48 MiR-BART6-3p avoids RIG-I recognition by targeting RIG-I (a pattern recognition receptor), evades the host's innate immune response, and promotes EBV infection. 172 MiR-557 is highly expressed in human megakaryocytic leukemia cells and plasma of children with ITP, its inhibitors improve ITP by regulating apoptosis-related genes and cellular immunity and activating Akt/ERK pathway.…”
Section: Megakaryocytes and Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, miR-29s have been recognized as one of the miRNAs that play a role in BL pathogenesis [145,146,147]. MiR-29s, which are downregulated in BL [65,80,121,148], regulate the expression of miRNA target genes, and their dysregulation leads to an imbalance of cellular pathways [149].…”
Section: Predicted Models Of Ffls Among Myc Its Targets and Mirnmentioning
confidence: 99%